Convergent transcription interferes with expression of the copy number control gene, copA, from plasmid R1 - Stougaard, Peter (EMBO J, 1982)
The copy number control gene, copA, of plasmid R1 codes for an 80-nucleotide untranslatable RNA. In Escherichia coli minicells, some copA hybrid plasmids and R1 miniplasmids also express a transcript of ˜200 nucleotides. Only the small RNA mediates the CopA phenotype. The switch between 80- and 200-nucleotide RNA synthesis is shown to be caused by convergent transcription; if transcription proceeds in both directions the inactive larger RNA is synthesised; the active small RNA is formed when copA transcription is not opposed by transcription from the other direction. The data presented indicate that convergent transcription interferes with copA expression by abolishing or reducing normal copA transcription termination. IMAGES: